Biochemical Study of Wild and Cultivated Blackcurrant (Ribes nigrum L.) berries - Munkhjargal, Odonchimeg; Byambaa, Munkhtsetseg; Damdindorj, Mungunnaran; Barkhuu, Bayarmaa (Mongolian Journal of Agricultural Sciences, 2021)
From over 150 species of berries belong to family Grossulariceae and genus Ribes, blackcurrants (Ribesnigrum L.) arewidely used, yet most beneficial berries in traditional medicine as well as in food. Blackcurrant berries known for not only for their extended storage of Vitamin C, but also high content of biologically active ingredients. Vitamin C stored in blackcurrant berries is relatively stable, does not get degraded during plantation, supports immune system, and has detoxicant and antioxidant properties. In this research we studied certain biochemical properties of cultivated, and blackcurrant berries grown in wild. We determined total carbohydrates 13.6-15.8%, simple carbohydrates 10.8-11.9%, total phenols 339.2-514.4 mg/g, total flavonoids 105.0-320.0 mg/g, and vitamin C 239-305 mg/% contained in cultivated, as well in wild blackcurrant berries. These results demonstrate the feasibility of producing all-natural biologically active compounds that support health from juices of both cultivated, and wild blackcurrant berries. Зэрлэг болон таримал үхэр нүд (Ribes nigrum l.) жимсний биохимийн судалгаа Үхэр нүд (Ribesnigrum L.) жимс нь Сэрдэгийн овог, Тошлойн төрөлд хамаарах 150 гаруй зүйлээс уламжлалт анагаах ухаан болон хүнсэнд өргөн ашиглагддаг чанараараа хамгийн их ач холбогдолтой жимсний нэг юм. Үхрийн нүд жимс нь маш урт хугацааны туршид витамин С-гийн баялаг эх сурвалж гэдгээрээ танигдсанаас гадна, биологийн идэвхт бодисыг өндөр тунгаар агуулдаг. Түүнд агуулагдах витамин С нь харьцангуй тогтвортой ба ургалтын явцад задардаггүй онцлогтой бөгөөд дархлаа дэмжих, биеийг хоргүйжүүлэх болон антиоксидант үйлдэлтэй. Энэхүү судалгаагаар тарималжуулсан үхэр нүд жимсний биохимийн бүрдлийг байгалийн зэрлэг жимстэй харьцуулан судлав. Судалгааны үр дүнд таримал болон зэрлэг үхэр нүд жимсэнд нийт нүүрсус 13.6-15.8%, энгийн нүүрсус 10.8-11.9%, нийт фенолт нэгдэл 339.2- 514.4 мг/г, нийлбэр флавоноид 105.00-320.0мг/г тус тусагуулагдаж байгааг тодорхойллоо. Витамин С, В1, В6,органик хүчлийн агууламжийг өндөр мэдрэмжит шингэний хроматограф (HPLC)-ын багажийг ашиглан тодорхойлов. Түлхүүр үг: Ribes nigrum L, жимс жимсгэнэ, антиоксидант, флавоноид,